Study of biofilm formation in clinical bacterial isolates of urinary tract infection. - Al-kayali, Rawaa (Latakia University Journal -Medical Sciences Series, 2018)
The present study was carried out to evaluate Biofilm production among urinary tract infection. A total of 53 bacterial isolates were included in the study. The identification and antibiotic susceptibility testing of all the isolates was done as per the standard laboratory protocol. Biofilm production was detected by adherence to test tubes. Among 53 isolates Escherichia coli 39.6%, Klebsiella pneumoniae 24.5%, Citobacter spp.15%, Pseudomonas spp 9.4 % and Coagulase- negative (CoN) Staphylococcus 11.3%. Considering the antibiotic susceptibility pattern 47.2% of isolates were multidrug resistant. Among MDR strains, 80% of isolates were found to be biofilm producers. Microbial biofilms have been associated with a variety of persistent infections which respond poorly to conventional antibiotic therapy. Hence detection of biofilms for all the isolates on a routine basis will help to choose effective treatment to eradicate bacteria and prevent further antibiotic resistance. دراسة تكون الغشاء الحيوي في العزلات الجرثومية السريرية المسببة لإنتانات الجهاز البولي هدفت هذه الدراسة لتقييم قدرة الجراثيم المعزولة من إنتانات الجهاز البولي على تكوين الغشاء الحيوي . شملت الدراسة 53 عزلة تم تعريفها واختبار حساسيتها للمضادات الحيوية بالطرائق المعتمدة. تم اختبار قدرة العزلات على تكوين الغشاء الحيوي باستخدام طريقة الالتصاق على الأنبوب. بلغت نسبة العصيات القولونية المعزولة 39.6% والكليبسيلا الرئوية 24.5% و الستروباكتر 15%و السيدوموناس 9.4% في حين بلغت نسبة عزلات المكورات العنقودية سلبية المخثراز 11.3%. بلغت نسبة العزلات المتعددة المقاومة للمضادات الحيوية 47.2% ، كان منها 80% مكوناً للغشاء الحيوي. إن تكوين الأغشية الحيوية من قبل الجراثيم الممرضة ارتبط بالعديد من الأمراض المزمنة التي لا تستجيب للعلاج التقليدي بالمضادات الحيوية. إن تشخيص قدرة العزلات على تكوين الغشاء الحيوي بشكل روتيني سوف يساعد على اختيار العلاج الفعال للقضاء على هذه الجراثيم ومنع انتشار المقاومة للمضادات الحيوية.